(3MRH GdHMQs - (3GdTGPdj, CHh GdMSf, fhQ GdOjf, Ydj Hf YHO Gddg Hf YHO GdLHGQ, J(B656(3g`s ((3edG eMeO Hf UGdMs)
(3ChdgG (B:s
(3jG Ydj jG YXje jG Mdje jG Ydje jG LhGO jG cQje jG ZahQ jG QMje jG s
(3BNQgG (B:s
(3SdGe Ydjce HeG UHQJe afYe YbHi GdOGQ SdGe gj MJi eWdY GdaLQ HQMeJc jG CQMe GdQGMejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 305s
(3eYLe GdeDdajf(B: 2 / 467s
(3cTa GdXfhf(B: 1 / 661s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs